The Centre of Excellence for Transport Service and Control - Gnap, Jozef; Kalasova, Alica; Gogola, Marian; Ondrus, Jan (Communications - Scientific letters of the University of Zilina, 2010)
The Centre of Excellence at the University of Zilina was established in 2009 as a new approach to research supported by EU. This model has been acknowledged around the EU as a highly effective way to strengthen a country’s research capacity, build partnerships and translate discoveries and advances into economic prosperity and a better quality of life for all citizens. The Centre of Excellence for transport service and control at the Faculty of Operation and Economics of Transport and Communications at the Department of Road and Urban Transport consists of the laboratory of transport service, laboratory of mass passenger transport control and laboratory of freight transport. The main objectives of these laboratories are presented in this article.